Trust Drives Internet Use - Martin Ljunge (Research Institute of Industrial Economics (IFN), 2012)
This paper estimates the effect of trust on internet use by studying the general population as well as second generation immigrants in 29 European countries with ancestry in 87 nations. There is a significant positive effect of trust on internet use. The positive trust effect is not universal to all media, as individuals with high trust are shown to consume less television. The finding provides evidence for one mechanism through which trust creates good outcomes. Individuals with high trust spend time online, and eschew the isolation of the TV couch, which may produce more productive opportunities.
Keywords: D13; D83; J62; Z13; 330; Trust; Internet use; Intergenerational transmission; Cultural transmission; TV watching; Internetnutzung; Fernsehnutzung; Vertrauen; Generationengerechtigkeit; Social Capital; Europa